2018
DOI: 10.1016/j.concog.2018.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Role of implicit learning abilities in metaphor understanding

Abstract: Although the use of metaphors is a central component of language, the processes that sustain their comprehension have yet to be specified. Work in the fields of both metaphors and implicit learning suggests that implicit learning abilities facilitate the comprehension of metaphors. However, to date, no study has directly explored the relationships between the understanding of metaphors and so-called implicit learning tasks. We used a meaning decision task comparing literal, metaphorical and meaningless express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…This interpretation of our results is supported by a previous study ( Drouillet et al, 2018 ) in which we showed that the gap between typical patients and meaningless patients was predicted by individual differences in implicit procedural memory abilities. We also showed that these individual differences predicted the ability to understand verbal metaphors, namely metaphors involving a verb and a patient (e.g., “catapulted his words”).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This interpretation of our results is supported by a previous study ( Drouillet et al, 2018 ) in which we showed that the gap between typical patients and meaningless patients was predicted by individual differences in implicit procedural memory abilities. We also showed that these individual differences predicted the ability to understand verbal metaphors, namely metaphors involving a verb and a patient (e.g., “catapulted his words”).…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, another view could be that this effect (also) depends on declarative memory. Indeed, when a verb is activated, some of its activation is thought to spread to its most typical patients due to the spreading activation process ( Kintsch, 2001 ; Drouillet et al, 2018 ). The developmental invariance hypothesis can help to delineate between these two memory systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential way to understand this result may be found in regarding individual differences in the ability to identify the correlation between waking events and dream reports. There is evidence suggesting that when confronted with novel metaphors, participants with higher implicit learning abilities are better able to identify that the expressions have some meaning (Drouillet, Stefaniak, Declercq, & Obert, 2018). Lakoff (1993) proposes that dreams are structured by an unconscious metaphor system, picturing waking‐life experiences and emotions in non‐literal, figurative ways.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential way to understand this result may be found in regarding individual differences in the ability to identify the correlation F I G U R E 3 The correlation between implicit learning ability and the averaged Similar-Feature-score between personally significant event and dream report TA B L E 1 Regression analysis for the averaged Matching-Score of PSEs-dreams pairs as predicted by the implicit learning ability, averaged dream length and the averaged Event-Emotionality-score between waking events and dream reports. There is evidence suggesting that when confronted with novel metaphors, participants with higher implicit learning abilities are better able to identify that the expressions have some meaning (Drouillet, Stefaniak, Declercq, & Obert, 2018). Lakoff (1993) proposes that dreams are structured by an unconscious metaphor system, picturing waking-life experiences and emotions in non-literal, figurative ways.…”
Section: Correlation Between Implicit Learning Ability and The Incorporation Of Waking Events Into Dreamsmentioning
confidence: 99%